THE ROLE OF SYSTEMS IN MAINTAINING THE MOST VALUABLE UNIVERSITY ASSETS CASE STUDY IN AIRLANGGA UNIVERSITY - JEFFITS KHUSNU ALIF; NOORLAILY SEWARNO; ISNALITA ISNALITA (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
This research focuses on the status of the lecturer as the foundation of a University , because the have the responsibility to educating a new generation that could bring pride to University, so there is no doubt that lecturer could be called the most valuable asset of the University. This research is a case study research with intepretif paradigm, which aim to determine the extent to which the result of a student evaluation of lecturer that measured by Airlangga University cybercampus questionnaires used as references by it’s lecturer and faculty. In desaigning lectures, faculty chooses a method that fit independently with each student in a class, but the method that is frequently used is a method that fit’s the teaching style of a lecturer, so there is small possibility of a significant change in the quality of teaching.